The Role of Employer Value Proposition (EVP) in Enhancing Competency and Loyalty of Public Employees: A Systematic Literature Review - Syah, Ramlan; Navigasi Belawan (urn:multiple://2988-7828multiple.v3i64)
Public sector organizations are increasingly challenged to recruit, nurture, and retain skilled civil servants due to generational shifts in the workforce, constrained career advancement opportunities, and heightened competition from the private sector. This study aims to systematically examine the role of Employer Value Proposition (EVP) in enhancing the competency and loyalty of public employees (ASN) as a strategic response to those challenges. A Systematic Literature Review (SLR) method guided by the PRISMA protocol was applied by analyzing scientific publications from top-tier international journals and reputable national journals. The review process involved identifying, screening, and synthesizing literature related to EVP, employer branding, competency development, and human capital in the public sector. The results show that a well-formulated EVP—comprising career development opportunities, inclusive work culture, organizational reputation, and work-life balance—significantly contributes to strengthening employee loyalty and competency enhancement. Furthermore, employer branding serves as a key instrument in positioning public institutions as attractive workplaces, particularly for younger generations. Competency-based talent development was also found to reinforce human capital strategies aligned with institutional missions. This review offers evidence-based insights for public sector leaders to integrate EVP into human resource management practices and promote sustainable employee engagement and capability growth.